A systematic review and meta-regression of temporal trends in the excess mortality associated with diabetes mellitus after myocardial infarction. (15th August 2016) - Bauters, Christophe; Lemesle, Gilles; de Groote, Pascal; Lamblin, Nicolas
Abstract: Background/objectives: It is not well known whether the gap in outcomes after myocardial infarction (MI) between patients with and without diabetes mellitus (DM) has changed over time. We performed a systematic review and metaregression of temporal trends in the excess mortality associated with DM after MI. Methods: We searched the PubMed database for studies reporting mortality data according to diabetic status in patients hospitalized for MI or acute coronary syndromes (ACS). We included 139 studies/cohorts for analysis (432, 066 diabetic patients and 1, 182, 108 nondiabetic patients). Results: When compared to their non-diabetic counterparts, patients with DM had an odds ratio (OR) [95% CI] of 1.66 [1.59–1.74] ( P < 0.0001) for early mortality, and of 1.86 [1.75–1.97] ( P < 0.0001) for 6–12 months mortality. When all data from the 116 studies reporting early mortality were pooled, there was no significant relationship between calendar year and Log (OR). Likewise, when considering the 61 studies reporting 6–12 months mortality, there was no significant relationship between calendar year and Log (OR). Similar to the overall pooled analysis, no significant relationship between inclusion year and Log (OR) for mortality in diabetic patients was observed in sensitivity analyses performed in studies with ST-elevation MI as inclusion criteria, in randomized trials, in studies including > 2000 patients, and in studies with DM prevalence > 20%. Conclusions: We found no evidence for temporal changes in the incremental mortality risk associated with DM in the setting of MI. The improvements in management of MI patients during the last decades have not been associated with a reduction of the gap between diabetic and non-diabetic patients.